ESTIMATION OF YELLOWFIN TUNA PRODUCTION LANDED IN BENOA PORT WITH WEIGHT-WEIGHT, LENGTH-WEIGHT RELATIONSHIPS AND CONDITION FACTOR APPROACHES - Irwan Jatmiko; Hety Hartaty; Budi Nugraha (Indonesian Fisheries Research Journal, 2016)
Yellowfin tuna (Thunnus albacares) is one of the important catch for the fishing industry in Indonesia. Length-weight relationship study is one of important tools to support fisheries management. However it could not be done to yellowfin tuna landed in Benoa port since they are in the form of gilled-gutted condition. The objectives of this study are to determine the relationship between gilled-gutted weight (GW) and whole weight (WW), to calculate length weight relationship between fork length (FL) and estimated whole weight (WW) and to assess the relative condition factor (Kn) of yellowfin tuna in Eastern Indian Ocean. Data were collected from three landing sites i.e. Malang, East Java; Benoa, Bali and Kupang, East Nusa Tenggara from January 2013 to February 2014. Linear regression analysis applied to test the significance baseline between weight-weight relationships and log transformed length weight relationship. Relative condition factor (Kn) used to identify fish condition among length groups and months. The results showed a significant positive linear relationships between whole weight (WW) and gilled-gutted weight (GW) of T. albacares (p<0.001). There was a significant positive linier relationships between log transformed fork length and log transformed whole weight of T. albacares (p<0.001). Relative condition factor (Kn) showed declining pattern along with length increase and varied among months. The findings from this study provide data for management of yellowfin tuna stock and population.